Exploring the grammatical complexity of L2 on non-English major learners’ writing: taking engineering students as a case study - Barbara Wing Yee Siu; Muhammad Afzaal; Hessah Saleh Aldayel; Qiuhan Lin (Humanities & Social Sciences Communications)
Abstract Over the past 10 years, the subject of grammatical complexity has attracted significant global interests. The present study employs the Register-Functional approach, shedding light on grammatical variations in the written mediums. Leveraging three corpora (i.e., the British Academic Written English corpus (BAWE), CEE corpus, and the Arab corpus), this study compares the writing assessment of native and L2 English students throughout their university tenures and across disciplines. It integrates inferential statistics with descriptive metrics to delve into correlations between the students’ academic year, the utilization of linguistic attributes, and the patterns framing their usage over time. Results found that while native speakers largely present stage 2 complexity, Chinese engineering students from the CEE corpus primarily display stage 3 grammatical complexity. The Saudi corpus, though taught in English, follows a similar yet distinct trend. While English continues to be championed as a medium of instruction, the clear divergence in writing structures between L1 and L2 writers accentuates the imperative for linguistic progression in L2 learners.